ANALISIS FAKTOR KEPERCAYAAN, KEMUDAHAN PENGGUNAAN DAN KUALITAS INFORMASI DALAM MEMENGARUHI PERILAKU BERBELANJA ONLINE MENGGUNAKAN SHOPEE - Mardiana, Dika; Ali, Suprihatin; Nugeraha, Prasetya (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2025)
This study aims to analyze the factors that influence Lampung University students to shop online using Shopee's E-Commerce. The research design is a qualitative case study using interviews, observation and documentation as data collection techniques. Interviews were conducted openly, semi-structured, and not in a formal setting to ten informants, eight of whom were consumers/buyers and two other informants were sellers/sellers using Shopee users. The data collected in this study was then reduced by grouping important data related to the research objectives. The results of the analysis show that in influencing online shopping behavior using Shopee, trust factors include address clarity, clarity of products sold, online store honesty in providing product information, and providing security guarantees in transactions, it is known that consumer trust in the Shopee online site is an important part and integral in purchasing decision making efforts. Shopee is able to provide convenience by creating features that can make it easier for consumers to search, select, and pay for products to be purchased. The product information submitted is not a guarantee for consumers in making online purchasing decisions using Shopee.